Measurement of the Breadth of the Thyroid Lamina in A Bangladeshi Population by Dissection Method - Ara, Anjuman; Ara, Zubaida Gulshan; Begum, Taslima; Mili, Dilruba Afrose; Naher, Kamrun (Community Based Medical Journal, 2022)
A cross-sectional, descriptive study was done to determine the breath of the thyroid lamina and the differences in its values in respect of age and sex in Bangladeshi cadavers. A total 60 postmortem human larynges were collected between October 2008 and March 2009. Among those, 45 (male 23 and female 22) were collected from unknown dead bodies (aged between 9 and 60 years) under autopsy in the mortuary of Department of Forensic Medicine of Mymensingh Medical College, while the other 15 (male 6 and female 9) were collected from stillborn babies of viable age (28 to 40 weeks of gestation) in the Department of Obstetrics & Gynaecology of Mymensingh Medical College Hospital, Mymensingh, Bangladesh. The breath of thyroid lamina was measured from laryngeal prominence to the posterior margins of lamina at its transverse plane using slide calipers and differences were observed in between age groups and sexes. The mean±SD breadth of thyroid lamina was found 12.40±1.30 mm in group A (from 28 to 40 weeks of gestation) ranging between 9 and 14 mm, while 26.19±3.69 mm in group B (from 9 to 16 years) ranging between 21 and 35 mm, and 30.76±4.17 mm in group C (from 17 to 60 years) with a range of 24 to 38 mm. The mean breadth of thyroid lamina was highest in age group C (30.76 mm) and was lowest in age group A (12.40 mm). The mean difference of breadth of thyroid lamina between group A & B, A & C and B & C were statistically significant (P=0.000). The breadth of thyroid lamina was found higher in male (32.70±3.96 mm) than that of female (28.00±2.69 mm) in Group C and the difference was statistically significant (p=0.001). Our study revealed that the breadth of thyroid lamina is greater in adult male than female and overall, the value increases with age. CBMJ 2022 July: vol. 11 no. 02 P: 131-135